Regarding Reality: Some Consequences of Two Incapacities - Edelman, Shimon (Frontiers in Psychology, 2011)
By what empirical means can a person determine whether he or she is presently awake or dreaming? Subjecting the experienced reality to a statistical test for bizarreness requires a set of baseline measurements. In a dream or in a simulation, those would be vulnerable to tampering by the same processes that give rise to the experienced reality, making the outcome of a reality test impossible to trust. Moreover, cryptographic defenses against tampering cannot be relied upon, because of the potentially unlimited reach of reality modification, which may range from the integrity of the verification keys to the declared outcome of the entire process. Although the rational course of action in the face of this double predicament is to take reality at face value, even the most revealing insight that a person may gain into the ultimate nature of reality (for instance, by attaining enlightenment) is ultimately unreliable, for the reasons just mentioned. However, to adhere to this principle, one has to be aware of it, which may not be possible in various states of altered cognitive function (e.g., dreaming). Thus, a subjectively enlightened person may still lack the one truly important piece of the puzzle concerning his or her existence.